-8m+32=-m-3(1+4m)

Simple and best practice solution for -8m+32=-m-3(1+4m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8m+32=-m-3(1+4m) equation:



-8m+32=-m-3(1+4m)
We move all terms to the left:
-8m+32-(-m-3(1+4m))=0
We add all the numbers together, and all the variables
-8m-(-m-3(4m+1))+32=0
We calculate terms in parentheses: -(-m-3(4m+1)), so:
-m-3(4m+1)
We add all the numbers together, and all the variables
-1m-3(4m+1)
We multiply parentheses
-1m-12m-3
We add all the numbers together, and all the variables
-13m-3
Back to the equation:
-(-13m-3)
We get rid of parentheses
-8m+13m+3+32=0
We add all the numbers together, and all the variables
5m+35=0
We move all terms containing m to the left, all other terms to the right
5m=-35
m=-35/5
m=-7

See similar equations:

| x*3/7=4 | | 80-5(y-1)=0 | | -148+3x+4x=111 | | 17=x2+8x-50 | | Y=2x-34 | | x/7+6=-5 | | 4x+20=85 | | 3x-12=3(x+1-15 | | -32x-59=-27 | | 8(2-x)=48 | | 3s/10=12 | | x3-4=5 | | 0x+86=100 | | 2(a+4)+4×4=10 | | B=y+20 | | -9-2x=4(8+7x) | | 7y+5=3y-2 | | 5z–8=32 | | -9-2x=4(8+7x | | 0.66=2^x | | 17-y=-1 | | 1-y=(10) | | -3(9x+7)-3=9x+2 | | Z+5=14-2z | | 2(a+4)+4*4=10 | | 23a-7=15 | | -14x-32=-18 | | -12=-24y | | 6=a÷4+2 | | 7-4m=-7 | | 0.5x+0.5=0.125 | | 6(4+8a)=-120 |

Equations solver categories